Fusobacterium Species in Osteoarticular Infections in Childhood—A Systematic Review with Data Synthesis and a Case Series in the Acetabular and Hip Joint Regions - Heide Delbrück; Silvia Schröder; Tom Stapper; Sabine Schacht; Angeliki Pappa; Frank Hildebrand; Miriam Katharina Hertwig (Infectious Disease Reports)
Background: In paediatric osteoarticular infections, microorganism detection is unsuccessful in up to 55% of cases, which is not satisfactory for targeted antibiotic therapy. In particular, anaerobic fusobacteria may be underdiagnosed owing to a lack of knowledge about their properties. Methods: Based on three of our own cases and a systematic literature review regarding paediatric osteoarticular fusobacterial infections, we extracted characteristic variables and synthesised them in terms of frequencies and mean comparisons. We followed the CARE and PRISMA guidelines. Results: In our three patients with hip area infections (aged 11, 12, and 16 years; two males and one female; two with Fusobacterium nucleatum [FNU] and one with Fusobacterium necrophorum [FNE]), we only detected FNU with PCR. The patient with an FNE infection showed a septic and protracted course with six surgical interventions and secondary coxarthrosis during the follow-up. The FNU infections were milder and healed without sequelae. In the literature, there are no articles with more than 3 cases; overall, we identified 38 case reports and 3 case series with a total of 45 patients. Across all synthesised cases (73% boys), the age was 9.2 ± 4.1 years. Most patients (42%) were affected by hip joint arthritis, with or without accompanying acetabular or femoral osteomyelitis, followed by knee joint arthritis, with or without osteomyelitis, in 24% of patients. In 49% of cases, there was an ear, nose, and throat focus. Depending on the affected structure, arthrotomy (33%), arthroscopy (11%), bone (24%), and soft tissue (9%) debridement were performed, with 34% of the procedures having to be performed several times. Penicillins, metronidazole, and clindamycin were the most used antibiotics. In 32 cases (71%), the authors reported healing without sequelae. Conclusions: When samples are collected in the operating theatre for paediatric osteoarticular infections, orthopaedic surgeons should also ensure correct anaerobic sampling and consider the possibility of performing PCR. A typical child with an osteoarticular fusobacterial infection is a boy of approximately 10 years of age with an infection in the hip area and a previous infection in the ENT area.